Aerobic Exercise Training Reduces Atherogenesis Induced by Low-Sodium Diet in LDL Receptor Knockout Mice - Ana Paula Garcia Bochi; Guilherme da Silva Ferreira; Vanessa Del Bianco; Paula Ramos Pinto; Letícia Gomes Rodrigues; Mayara da Silva Trevisani; Luzia Naoko Shinohara Furukawa; Kely Cristina Soares Bispo; Alexandre Alves da Silva; Ana Paula Pereira Velosa; Edna Regina Nakandakare; Ubiratan Fabres Machado; et al. (MDPI AG, 2022)
This study investigated the efficacy of aerobic exercise training (AET) in the prevention of dyslipidemia, insulin resistance (IR), and atherogenesis induced by severe low-sodium (LS) diet. LDL receptor knockout (LDLR KO) mice were fed a low-sodium (LS) (0.15% NaCl) or normal-sodium (NS; 1.27% NaCl) diet, submitted to AET in a treadmill, 5 times/week, 60 min/day, 15 m/min, for 90 days, or kept sedentary. Blood pressure (BP), plasma total cholesterol (TC) and triglyceride (TG) concentrations, lipoprotein profile, and insulin sensitivity were evaluated at the end of the AET protocol. Lipid infiltration, angiotensin II type 1 receptor (AT1), receptor for advanced glycation end products (RAGE), carboxymethyllysine (CML), and 4-hydroxynonenal (4-HNE) contents as well as gene expression were determined in the brachiocephalic trunk. BP and TC and gene expression were similar among groups. Compared to the NS diet, the LS diet increased vascular lipid infiltration, CML, RAGE, 4-HNE, plasma TG, LDL-cholesterol, and VLDL-TG. Conversely, the LS diet reduced vascular AT1 receptor, insulin sensitivity, HDL-cholesterol, and HDL-TG. AET prevented arterial lipid infiltration; increases in CML, RAGE, and 4-HNE contents; and reduced AT1 levels and improved LS-induced peripheral IR. The current study showed that AET counteracted the deleterious effects of chronic LS diet in an atherogenesis-prone model by ameliorating peripheral IR, lipid infiltration, CML, RAGE, 4-HNE, and AT1 receptor in the intima-media of the brachiocephalic trunk. These events occurred independently of the amelioration of plasma-lipid profile, which was negatively affected by the severe dietary-sodium restriction.